The Role Of Parents In Learning Local Culture Of Little Gamelan In Early Childhood - Joko Pamungkas (Eduvest - Journal of Universal Studies, 2021)
This study aims to reveal the relationship between the role of parents in learning local culture of little gamelan in early childhood. This study uses quantitative methods with collecting data by asking questions or interviewing parents, observing with documentation on group B children in TK ABA Ngabean 2, Yogyakarta. The results of this study show that the level of closeness of the relationship between the role of parents and learning of local gamelan little gamelan culture is very high seen from the results of the correlation count, which is 0.9994 or close to 1. and a positive correlation sign indicates a perfect linear relationship and the line has a positive slope. The data shows that as X or the role of parents increase, the results of the y value will increase or learning the local culture of the little gamelan. The family environment as a place for the first education for children. Children at the age of 0-6 years is a period when children are sensitive to everything. Therefore, in this case, learning the local culture of little gamelan is good to do at this time.